OneWorldMarket - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
OneWorldMarket launched in the Netherlands in November 2002 promotes sustainable trade and production chains via its Internet platform, encouraging collaboration between entrepreneurs and civil society organisations in the North and the South.